Pengaruh Waktu Fermentasi dan pH Terhadap Kandungan Nitrogen, Kalium, dan Fosfor dalam Pupuk Cair Organik Dari Limbah Kulit Pisang (Musa paradisiacal) - Mubarokah Nuriaini Dewi; Dody Guntama; Rizky Perdana; Muhammad Fauzan (Program Studi Teknik Kimia, Universitas Pamulang, 2022)
Fruit peel waste is a big problem nowadays because the production of waste is getting bigger as the population grows. On the other hand, fruit peel waste contains elements of N, P, K which can be used to make organic fertilizer. This research was conducted by mixing water, banana peel waste and EM-4 bacteria with the fixed variables used were banana peel waste and the amoufant of EM-4 bacterial bio activator while the independent variables used in this study were the fermentation time for (2 days, 4 days and 6 days). days), with variations in initial pH (4 and 5). Testing of organic fertilizers was carried out based on the standard method of SNI 2803. Testing of nitrogen content using the Kjeldahl method, phosphorus levels as P2O5 using a UV-Vis Spectrophotometer, potassium as K2O using an Atomic Absorption Spectrophotometer (AAS) instrument. The results showed that the best level of nitrogen was 1,297.43 ppm and the best level of phosphorus was 86 ppm which was produced on the second day of fermentation with a variation of initial pH 4. While the best potassium level was obtained by a variation of initial pH 5 at a fermentation time of 6 days, namely 11,735.6 ppm. Based on the analysis of the levels of N, P, K that was carried out, the organic fertilizer produced did not meet the SNI specifications.